Investigation of Si-based thermoelectrochemical cells (TECs) towards semiconductor fabrication and processing. (4th October 2021) - Megat Hasnan, M M I; Nayan, N; Ahmad, M K; Mohd Zin, R; Fhong, S C; Said, S M; Mohamed Ali, M S; Mohd Sabri, M F; Mohamad, K A; Mohd Salleh, M F
Abstract: Thermoelectrochemical cells (TECs) are an alternative with potential for micro-power generator applications but is rarely fabricated using semiconductor processes or micro-fabrication technology. This study initiates fabrication of a Si-based TEC cell device using micro-fabrication technology. The iodide/triiodide poly(vinyl alcohol) hydrogel polymer electrolyte, and citric acid as supporting electrolyte, is selected as the TEC material. A platinum electrode sputtered on a silicon substrate is used as the hot and cold electrode. The TEC voltage generation that is based on Soret diffusion and the Seebeck effect shows good repeatability and stability. The magnitude of the power density shows dependence on the device electrode separation and temperature difference. At 10 mm electrode separation and a temperature difference of 30 K, the Si substrate TEC is able to produce 310 µ W m −2 ; thus, it shows high potential as a low heat waste Si-based TEC power generator.